2019
DOI: 10.1615/computthermalscien.2019026405
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Transient Radiative Reactive Thermosolutal Magnetohydrodynamic Convection in Inclined MHD Hall Generator Flow With Dissipation and Cross Diffusion

Abstract: Ti t l eCo m p u t a tio n of t r a n si e n t r a di a tiv e r e a c tiv e t h e r m o-s ol u t al m a g n e t o hy d r o dy n a mi c c o nv e c tio n in inclin e d m h d h all g e n e r a t o r flow wi t h di s si p a tio n a n d c r o s s diffu sio n A u t h o r s B e g, OA, S h e ri, S R, M o d u g ul a, P a n d Ka dir, A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The negative nature of this term indicates destructive chemical reaction and clearly, its augmentation will dampen the nanoparticle concentration values as a greater conversion of original species to a new product via chemical reaction will be induced with greater (Kr) values. Similar trends in magnetohydrodynamic boundary layer thermo solutal flows are presented by Sivaraj and Kumar [54,55], Kumar and Sivaraj [56], Sheri et al [57] and Beg et al [58]. Of course, extra complex chemical reactions may take place e.g.…”
Section: Resultssupporting
confidence: 74%
“…The negative nature of this term indicates destructive chemical reaction and clearly, its augmentation will dampen the nanoparticle concentration values as a greater conversion of original species to a new product via chemical reaction will be induced with greater (Kr) values. Similar trends in magnetohydrodynamic boundary layer thermo solutal flows are presented by Sivaraj and Kumar [54,55], Kumar and Sivaraj [56], Sheri et al [57] and Beg et al [58]. Of course, extra complex chemical reactions may take place e.g.…”
Section: Resultssupporting
confidence: 74%
“…A uniform radiative flux is applied transverse to the sheet plane. The polymer is assumed to absorb or emit radiation but not scatter radiation [32] and Rosseland's diffusion flux approximation, valid for high optical thickness is therefore deployed.…”
Section: Mathematical Model For Viscoplastic Non‐fourier Stretching P...mentioning
confidence: 99%
“…The novelty is embodied in the simultaneous inclusion of multiple magnetic effects, a sophisticated micromorphic non-Newtonian model, and an alternative computational algorithm (modified cubic B-Spline differential quadrature method) which has never been considered collectively in previous studies. Ionslip and Hall's current effects have been extensively studied by Bég and co-workers [51][52][53][54] in the context of nuclear reactor transport modeling and magnetohydrodynamic energy generators (MHD). These studies have confirmed the substantial modification in velocity and temperature distributions produced with Hall current and ion slip which are relevant to, for example, seeded potassium interfacial flows in Hall and Faraday generator systems [55][56][57][58] and also hydromagnetic pumps and channel flow control in nuclear reactors.…”
Section: Articlementioning
confidence: 99%